Comparison of Intra- and Postoperative 3-Dimensional Digital Subtraction Angiography in Evaluation of the Surgical Result After Intracranial Aneurysm Treatment. Issue 4 (21st November 2019) - Marbacher, Serge; Kienzler, Jenny C; Mendelowitsch, Itai; D'Alonzo, Donato; Andereggen, Lukas; Diepers, Michael; Remonda, Luca; Fandino, Javier
Abstract: BACKGROUND: Postoperative three-dimensional digital subtraction angiography (3D-DSA) is the gold standard in evaluating intracranial aneurysm (IA) remnants after clipping. Should intraoperative 3D-DSA image quality be equally good as postoperative 3D-DSA, it could supplant the latter as standard of care for follow-up of clipped IA. OBJECTIVE: To directly compare the quality of assessment of clipped IA by intraoperative and postoperative 3D-DSA. METHODS: From a prospective cohort of 221 consecutive patients who underwent craniotomy for IA treatment in a hybrid operating room, we retrospectively studied 26 patients who had both intraoperative and postoperative 3D-DSA imaging of their clipped aneurysm. Comparison of intraoperative and postoperative 3D-DSA images (blinded for review) included parameters that affected image quality and differences between the 2 periods. RESULTS: In the 26 patients with 32 clipped IAs, the mean interval was 11 ± 7 mo between intraoperative and postoperative imaging 3D-DSA examinations. Reconstruction with multiple clips was used in 14 (44%) cases. Of 15 remnants, 9 (60%) were small (<2 mm). In comparing intraoperative and postoperative 3D-DSA, no discordance or discrepancy in assessment of the surgical result was noted for any clipped IA, and overall imaging quality was excellent for both modalities. Factors affecting minor differences in image quality were not identified. CONCLUSION: Compared with postoperative 3D-DSA, intraoperative 3D-DSA images achieved equally high quality and effective, immediate interpretation of the surgical clipping result. With comparable imaging quality and no discordant findings, intraoperative 3D-DSA could replace postoperative 3D-DSA to become the standard of care in IA surgery.